Integrated Curriculum in Islamic School: Integration of Knowledge and Parental Involvement - Dardiri, Muhammad Amiruddin; Su’aidi, Mohamad Zaki (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2024)
Integrative education is one of the current trends in education models, especially integration in the curriculum aspect with a broad understanding, not only limited to the curriculum as a list of subjects but also learning experiences for students. This study aimed to analyze the implementation of integrated education in two aspects: first, the integration of knowledge, and second, the integrative role between school (teachers) and home (parents). This research was conducted using a qualitative approach at Al-Azhar Islamic School Solo Baru. Data collection techniques were conducted through interviews, observation, and documentation. Data analysis techniques used interactive analysis with steps: 1) data condensation, 2) data display, and 3) drawing and verifying conclusion. The results of the study showed: 1) Al-Azhar Islamic School harmonizes empirical sciences with religious sciences in the education process; 2) The process of integrating educators at home (parents) and at school (teachers) is an essential aspect of implementing an integrative curriculum. Well-educated parents can contribute to the children's education process at school.